PECULIARITIES OF INVESTMENT STRATEGIES OF JAPAN AND THE PROSPECTS OF COOPERATION WITH RUSSIA - A. V. Kuznetsov (Финансы: теория и практика)
Topic. Japan has excess financial resources and since the late 2000s is the second largest direct foreign investor in the world after the United States (except in 2014 and 2016, when Japan was down to 4th place). At the same time, Japan is not included in the 20 largest recipients of foreign direct investment (FDI). This imbalance is due to a combination of the expansion of Japanese multinational corporations (MNCs) in foreign markets with the traditional protection of domestic market from foreign competition, what differentiates Japan from other major players in Asia, primarily China, Hong Kong and Singapore. Such a synthesis of openness to the outside and closing from the inside largely allowed Japan to create and save your own unique self-contained culture of management and to introduce Western institutions without fear of the loss of a special national character.Purpose. Analysis of modern tendencies of economic development and investment processes of Japan with special emphasis on reviewing problems and prospects for Russian-Japanese investment cooperation.Methodology. There were used methods of scientific abstraction, statistical analysis, and logical generalization.Results. Large-scale stimulation of domestic demand through monetary, credit, and budgetary policies have not led to the expected recovery of the Japanese economy. The reason for the stagnation lies in a conservative approach to innovation while maintaining adherence to traditional production methods. The experience of Japan is of interest to Russia. Pursuing a strategy of advanced development of foreign trade sector in conditions of financial globalization, Japan attaches high priority to boosting domestic demand, to the development of the national financial market, and to the establishment of regional production networks. As the largest net investor in the world, Japan constantly diversifies sphere of foreign investments.Conclusions. The direction of Russian-Japanese cooperation in the sphere of joint implementation of significant innovative projects can have a long-term multiplier effect for the return of both economies to a trajectory of sustainable growth.